Green Synthesis of Silver Nanoparticles and their Potential Applications in Mitigating Cancer - Mir, Reyaz Hassan; Maqbool, Mudasir; Mir, Prince Ahad; Hussain, Md. Sadique; Wani, Shahid ud din; Pottoo, Faheem Hyder; Mohi-ud-din, Roohi (Current Pharmaceutical Design, 2024)
In recent years, the field of nanotechnology has brought about significant advancements that have transformed the landscape of disease diagnosis, prevention, and treatment, particularly in the realm of medical science. Among the various approaches to nanoparticle synthesis, the green synthesis method has garnered increasing attention. Silver nanoparticles (AgNPs) have emerged as particularly noteworthy nanomaterials within the spectrum of metallic nanoparticles employed for biomedical applications. AgNPs possess several key attributes that make them highly valuable in the biomedical field. They are biocompatible, cost-effective, and environmentally friendly, rendering them suitable for various bioengineering and biomedical applications. Notably, AgNPs have found a prominent role in the domain of cancer diagnosis. Research investigations have provided evidence of AgNPs' anticancer activity, which involves mechanisms such as DNA damage, cell cycle arrest, induction of apoptosis, and the regulation of specific cytokine genes. The synthesis of AgNPs primarily involves the reduction of silver ions by reducing agents. Interestingly, natural products and living organisms have proven to be effective sources for the generation of precursor materials used in AgNP synthesis. This comprehensive review aims to summarize the key aspects of AgNPs, including their characterization, properties, and recent advancements in the field of biogenic AgNP synthesis. Furthermore, the review highlights the potential applications of these nanoparticles in combating cancer.
Keywords: Green synthesis